What next for tests of the situational model of Situational Action Theory? Recommendations from a systematic review - Hardie, Beth (European journal of criminology, 2025)
Situational Action Theory's (SAT) situational model is being increasingly applied to study rule-breaking behaviours. Given this rapidly growing interest, it is timely to review the state of empirical support for the model and identify conceptual and methodological challenges in order to guide future studies in more appropriate tests of the model. This paper systematically reviews 37 quantitative tests of SAT's situational model that were published during the 5 years from 2016 to 2020 to formulate and then answer the following research questions: (1) What samples and offences have been studied to investigate the situational propositions put forward by SAT, and what are the most needed kinds of studies and replications? (2) What is the state of empirical support for SAT's situational model? (3) What are the challenges and what improvements are required for future tests of SAT's situational model? and (4) What clarifications and refinements are a theoretical priority? Overall findings of the review highlight the utility of SAT's situational model in investigating a diversity of rule-breaking behaviours across a range of ages and countries. However, the review also makes clear that when reviewed as a whole, this literature encounters methodological pitfalls and theoretical imprecision. These limitations must be addressed as empirical tests of SAT's complex situational model become increasingly nuanced and highly specified. Thus, building on the findings of the systematic review, the paper explores these complex limitations and specifies the theoretical and methodological refinements required to advance the study of person-environment interaction in acts of rule-breaking.